PLAYING ACTIVE VIDEO GAMES WHILE IN A TENNIS TRAINING PROCESS: A NEW TRAINING TOOL OR A HANDICAP FOR CHILDREN? - Luka Šlosar; Matej Plevnik; Uroš Marušič (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2018)
Aim: The purpose of this pilot study was to quantify the effect of a continued active video games (AVG) playing on the tennis forehand and backhand technique development. Methods: Altogether 24 tennis players (7 - 9 year olds) were randomly divided in two different groups, both involved in a 12-week tennis training program (twice a week for an hour). The participants in the experimental group received an additional twice a week (20-minute) AVG Virtua Tennis 4 game intervention at the end of each regular tennis training hour, while the participants in the control group received no additional intervention. Pre- and post-AVG intervention, the Tennis Rating Score for Children scale (TRSC) was applied to detect tennis training-related changes that occur in each specific stroke. Results: Our results at the post-test show that participants in the experimental group did not significantly improved in one element (TRSC12; p = 0,317) in the forehand stroke and two (TRSC10; p = 0,157 and TRSC12 p = 0,157) in the backhand. The control group significantly improved in all the fifteen evaluated elements in both the forehand and backhand stroke. The experimental group had a higher effect size in all the kinetic chain section in both the forehand and backhand stroke compared to the control. The same happens for the TRSC7 (point of contact - height). Conclusion: Prolonged AVG playing seems to improve visual attentions skills (perception of a moving object) in young tennis players, giving them the opportunity to be able to prepare themselves for the oncoming ball sooner as compared to their control counterparts. From the other perspective, AVG were shown to negatively affect correct players positioning, especially at the beginning and at the end of a stroke. Keywords: exergames, tennis technique, visual attention skill